Correlations between South African Red Grape and Wine Colour and Phenolic Composition: Comparing the Glories, Iland and Bovine Serum Albumin Tannin Precipitation Methods - du Toit, W.J.; Visagie, M. (South African Journal of Enology and Viticulture, 2016)
Phenolic compounds in red grapes might give an indication of phenolic and colour compositions of the resulting wine. This work compared the Glories, Iland and Bovine Serum Albumin (BSA) tannin precipitation methods for phenolic characterization of South African Pinotage, Merlot, Shiraz and Cabernet Sauvignon red grape samples (n=31). Significant positive correlations were found for certain phenolic characteristics in the grapes measured by these methods. Levels of phenolic compounds in the grapes and correlating wines were in line with literature. Merlot samples often associated more with higher concentrations of seed tannins, which were also reflected in the wines. Significant correlations were also found with the colour characteristics of the resulting wines and some anthocyanin related measurements in the grapes with the Glories and Iland methods, with the latter correlating slightly better. Significant positive correlations were also found between grape and wine tannins as measured with the BSA method. However, malolactic fermentation changed some of these correlations and this needs to be investigated further. This work might give wine producers as well as wine analyses laboratories valuable information regarding the suitability of these methods to characterize the phenolic composition of South African red grapes and their resulting wines.